2008
DOI: 10.1007/s11104-008-9666-5
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of spruce litter needles of different quality by Setulipes androsaceus and Thysanophora penicillioides

Abstract: Various biotic and abiotic factors may change the quality of cast spruce needles or induce premature casting, subsequently altering the composition of needle litter. We tested the decomposition efficiency of Setulipes androsaceus, a key litter decomposer in spruce forests, on needles of the Norway spruce (Picea abies) that fell into three different categories of quality. We designed a cultivation experiment to test the decomposition rate of the following needle categories: (1) naturally senesced brown needles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Zimmer and Topp (2002) also reported that frass of geometrid moth larvae fed on the leaves of beech trees was decomposed more rapidly than beech leaf litter. In general, insect frass has a higher concentration of N and labile C relative to leaf litter, which is considered to be one of the reasons for the rapid decomposition of frass (Lovett and Ruesink 1995;Madritch et al 2007; but see Koukol et al 2008). Values presented are means ± SE.…”
Section: Litter and Frass Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zimmer and Topp (2002) also reported that frass of geometrid moth larvae fed on the leaves of beech trees was decomposed more rapidly than beech leaf litter. In general, insect frass has a higher concentration of N and labile C relative to leaf litter, which is considered to be one of the reasons for the rapid decomposition of frass (Lovett and Ruesink 1995;Madritch et al 2007; but see Koukol et al 2008). Values presented are means ± SE.…”
Section: Litter and Frass Decompositionmentioning
confidence: 99%
“…Mixing of leaf litter and insect frass is likely to occur at the soil surface in temperate forests, where leaf litter accumulates easily on the forest floor due to the relatively slow rate of litter decomposition (Barbour et al 1998). However, it remains largely unknown how mixtures of leaf litter and insect frass, and their mixing ratio, influence the decomposition process (but see Frost and Hunter 2008;Koukol et al 2008). Regarding leaf litter decomposition, the decomposition of mixtures of litter produced by different plant species has been well examined, and many studies have demonstrated that mixtures of litter of multiple plant species showed non-additively enhanced decomposition efficiency, compared to that predicted from the litter of single species (Gartner and Cardon 2004;Ha¨ttenschwiler et al 2005;Gessner et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For inorganic P, orthophosphate was found in all samples but pyrophosphate was only found in the surface soil. Pyrophosphate was present in live fungal tissue and was easily decomposed (Koukol et al, 2008). In addition to inorganic P, the OP in the WECs of all depths for sample A and B contained similar species including orthophosphate monoesters (36-128 mg kg -1 ) and diesters (0-89 mg kg -1 ) according to NMR results (Table 3).…”
Section: Solution 31p Nmr Analysis and P K-edge Xanes Analysismentioning
confidence: 82%
“…are well known as saprophytes and as secondary pathogens of plants. T. penicillioides is listed as one of the most important species responsible for the decomposition of spruce needles [20]; this may easily explain its relatively high proportion in the air samples both inside and outside the bear dens. Penicillium spp.…”
Section: Resultsmentioning
confidence: 99%